2008
DOI: 10.1007/s10600-008-9108-x
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and Oleanolic Acid from Scabiosa caucasica

Abstract: In continuation of phytochemical investigations of plants of the Dipsacaceae family growing in the Republic of Azerbaidzhan [1, 2], we studied flowers of Scabiosa caucasica M.B. for flavonoid and triterpenoid content. Air-dried flowers (2 kg) collected during full flowering at the end of July 2006 near the village Slavyanka of Kedabek region of the Republic of Azerbaidzhan were extracted with ethanol (95%, 2×). The combined extracts were evaporated to 250 mL and left at room temperature. The resulting white pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…Total acid hydrolysis, UV, 1 H NMR, 13 C NMR, HSQC, HMBC, COSY and FAB-MS were consistent with the literature data (Mabry et al, 1970;Garaev et al, 2008). Thus compound 6 was identified as diosmetin-7-O-a-L-arabinosyl-(1 000 -6 00 )-bDglucopyranoside or palustroside.…”
Section: Characterisation Of the Isolated Compoundssupporting
confidence: 85%
“…Total acid hydrolysis, UV, 1 H NMR, 13 C NMR, HSQC, HMBC, COSY and FAB-MS were consistent with the literature data (Mabry et al, 1970;Garaev et al, 2008). Thus compound 6 was identified as diosmetin-7-O-a-L-arabinosyl-(1 000 -6 00 )-bDglucopyranoside or palustroside.…”
Section: Characterisation Of the Isolated Compoundssupporting
confidence: 85%
“…The majority of Scabiosa, comprising about 100 species, occurs in the Mediterranean region (Carlson et al, 2012) and among them, approximately 12 species can be found in Algeria (Quezel and Santa, 1963). Up to date, chemical investigations of Scabiosa species have mainly revealed the presence of saponins (Alimbaeva et al, 1977, Baykal et al, 1998, Zheng et al, 2004, flavonoids, coumarins (Garaev et al, 2008), and iridoid glucosides (Papalexandrou et al, 2003, Polat et al, 2010. The aglycone of Scabiosa saponins were identified as oleanolic acid, hederagenin, and ursolic acid with glucose, rhamnose, xylose, and arabinose as sugar , Yusifova and Movsumov 2015, Zheng et al, 2004, or pomolic acid with glycoside containing an allose in Scabiosa rotata saponins (Baykal et al, 1997, Baykal et al, 1998.…”
Section: Introductionmentioning
confidence: 99%
“…This compound was isolated at pure compound from S. tenuis Spruner ex Boiss, S. argentea L., S. atropurpurea L . S. caucasica M. B, S. ochroleuca L. and S. bipinnata C. Koch …”
Section: Resultsmentioning
confidence: 99%
“…[31] The glycosylated flavonoid, luteolin 7-O-glucoside, was identified for the first time in Scabiosa arenaria. This compound was isolated at pure compound from S. tenuis Spruner ex Boiss, S. argentea L., [28] S. atropurpurea L. [29] S. caucasica M. B, [32] S. ochroleuca L. and S. bipinnata C. Koch. [33] The third peak (compound 3) in the HPLC chromatogram ( Figure 3) was eluted at 20.5 min, exhibited a positive molecular ion at [MS+H] + at an m/z of 432.6 ( Figure 6a) and a positive fragment ion [MS 2 +H] + at an m/z of 270.7 (Figure 6b).…”
Section: Identification Of I 3 Subfraction By Nmrmentioning
confidence: 99%